Governamento linguístico em educação de surdos: práticas de produção do Surdus mundi no século XX - Witchs, Pedro Henrique (Universidade do Vale do Rio dos Sinos, 2018)
Acessível por código QR ou pelo endereço https://youtu.be/9NXA_zLLgGM

Starting from the matrix of experience concept to do a reading of the deafness, this doctoral dissertation presents an analysis of the ways in which the deaf are linguistically conducted. Within this aim, it uses a set of documents maintained by the Historical Collection of the National Institute of Deaf Education and that date back to the period between 1909 and 1989. From the perspective of authors in the fields of Foucaultian Studies and Deaf Studies in Education, as well as the Social History of Language and the Linguistic Policy, this dissertation makes use of the concepts of government and subjectivation as analytical tools. Based on the material analyzed, in this sense it was possible to distinguish linguistic government practices in two kinds of the deaf 's linguistic behavior: the desired language behavior and the abject language behavior. From each of the two behavior, practices of linguistic government were identified that had, as a purpose, the development of the nationality in the deaf. These practices were distributed in three compositions of the deaf education: the curriculum, the teacher training and the pedagogical practices. In view of this, it is argued that such practices operate in the production of a deaf subjectivity with universal characteristics of a linguistic behavior, the Surdus mundi, that, although it can use a sign language and is oriented to a cosmopolitan tendency to be deaf, covers in itself the possibility of be conducted also by the use of the oral languages although in its written modality. The doctoral dissertation contributes to thinking not only of the aspects of linguistic government in deaf education, but also in the education of any individual, and allows the promotion of discussions in the areas of Education and Linguistics.

Partiendo del concepto de matriz de experiencia para realizar una lectura de la sordera, la Tesis presenta un análisis de los modos por los cuales los sordos tienen sus conductas lingüísticas conducidas. Para ello, hace uso de un conjunto de documentos conservados por el Archivo Histórico del Instituto Nacional de Educación de Sordos que datan desde el año 1909 hasta 1989. Bajo la perspectiva de autores del campo de Estudios Foucaultianos, de Estudios Sordos en Educación y de la Historia Social de la Lengua y de la Política Lingüística utiliza los conceptos de gobernamento y de subjetivación como herramientas analíticas. Con base en el análisis de los documentos, fue posible distinguir prácticas de gobernamento lingüístico en dos grupos de caracterizaciones del comportamiento lingüístico de los sordos: las conductas lingüísticas anheladas y las conductas lingüísticas abyectas. A partir de cada una de las caracterizaciones, se identificaron prácticas de ejercicio del gobernamento lingüístico que tenían, como finalidad, el desarrollo de la nacionalidad en los sordos. Esas prácticas fueron distribuidas por tres elementos de la educación de sordos: el currículo, la formación de profesores y las prácticas pedagógicas. En este sentido, se defiende la tesis de que tales prácticas operan en la producción de una subjetividad sorda con características universales, el Surdus mundi, que, aunque pueda utilizar una lengua de señas y esté orientada a una tendencia cosmopolita de ser sordo, abarca en sí la potencia de ser gobernada también por el uso de lenguas orales, aunque en su modalidad escrita. La tesis no sólo contribuye en el debate de los aspectos del gobernamento lingüístico en la educación de sordos, sino también en la educación de cualquier individuo y fomenta las discusiones en las áreas de la Educación y de la Lingüística.
Keywords: Educação de surdos; Surdez; Língua; Governamento; Subjetivação; Deaf education; Deafness; Language; Government; Subjetivation; Educación de sordos; Sordera; Lengua; Gobernamento; Subjetivación; ACCNPQ::Ciências Humanas::Educação